Six projets pour l'urbanisme euroméditerranéen / Sei progetti per l'urbanistica euromediterranea - Carta, Massimo (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This book is conceived with the desire to dialogue with the southern shore of the Mediterranean Sea about some great current challenges in the fields of urban design and territorial planning. In this perspective, the authors identify six themes at the basis of the Italian disciplinary tradition, from which to extract suggestions for future projects. Some specific strategies emerge: the structuring role of the non-artificialized open space; the ordering function of the collective public space; the centrality of public action in the governance of transformations; the importance of multidisciplinary and integrated approach to problems; the heritage intended as a living repository of ideas for the project. Finally, the evocation of a limit between anthropogenic and natural factors that gives measure and dimension to our world.